An experimental approach to study the effect of wear on traction coefficient and dynamic response of roller bearing. (2021) - Kumar Prasad, Deepak; Amarnath, M.; Chelladurai, H.
Abstract: Cylindrical roller bearings are generally used to support rotating shafts mounted in a rotating machinery. These machine elements are prone to premature failure due to increase in friction which causes the heat generation and gradual wear on rolling contact surfaces of the bearing. Bearing failure leads to unexpected shutdown of machinery, therefore several condition monitoring methods have been developed to detect and diagnose the bearing faults. The purpose of this paper is to establish a relationship between surface roughness and wear on the traction coefficient parameter of roller bearing and corresponding dynamic response. Results obtained from the experimental investigations highlight dependency of traction coefficient and dynamic response of the bearing on wear propagation on the rolling contact surfaces.